A qualitative interview study of care home managers’ experiences of medicines optimisation for residents with dementia during the COVID-19 pandemic - Carmel M Hughes; Heather E Barry; Nawaf Alsulami (BMJ Open)
Objectives To explore care home managers’ views and experiences of optimising medicines use for residents with dementia during the COVID-19 pandemic.Design, setting and participants A descriptive exploratory qualitative study using semistructured interviews (conducted via telephone or online videoconferencing platform), with care home managers across Northern Ireland, purposively sampled from care homes that provided care for residents with dementia. Care home managers were asked to describe their experiences of accessing primary healthcare services (such as those provided by general practitioners and community pharmacists), how medicines use by residents with dementia was affected by the pandemic, and what they had learnt from their experiences. Data were analysed using inductive thematic analysis.Results Fourteen interviews were conducted between January and July 2022. Four themes, ‘isolation’, ‘burden’, ‘disruption’ and ‘connection and communication’, were identified; isolation was a cross-cutting theme that permeated the other themes. Care home managers described feeling isolated from healthcare professionals, healthcare services and residents’ family members. This isolation placed additional burden on care home staff and residents with dementia by increasing staff workload and negatively affecting residents’ well-being. Participants reported that disruption to primary healthcare service provision, particularly services provided by general practices, had significant impact on residents with dementia. Participants described a lack of face-to-face contact with healthcare professionals, and medication reviews often ceased to take place. The connection and communication between key stakeholders were perceived to be important when optimising medicines for residents with dementia.Conclusions This study has highlighted the challenges and initial impact of the COVID-19 pandemic on medicines optimisation for care home residents with dementia, which was characterised by isolation. Further research is needed to determine the extent of the long-term impact of the COVID-19 pandemic on this resident population. In future public health crises, better communication is needed between healthcare professionals and care homes.